Pola Keruangan Kapasitas Adaptasi Terhadap Bencana Penyakit Di Kota Semarang - Widjonarko Widjonarko; Maryono Maryono; Muhammad Lutfi Aliyudin (Ruang, 2018)
The city of Semarang is one of the big cities with the incidence of disasters especially dengue fever disease (DHF) is quite high. To reduce the incidence of DBD Semarang city government has done preventive action to improve clean and healthy life behavior, intensive socialization about mosquito nest eradication and home monitoring activities against the potential emergence of DBD through routine examination of potential water reservoir as a mosquito breeding. This effort is enough to show encouraging results with a decrease in the incidence of disease. But in 2017 there is an indication of the increase in the incidence of dengue disease when compared to the previous year. Based on this incident it is important to examine the level of adaptation capacity of the community against the occurrence of DHF. Based on the results of research, the adaptation capacity of Semarang City community has high adaptation capacity level with diffuse pattern. Low adaptation capacity has a pattern of gathering around North Semarang, Pedurungan and Gayamsari districts. This condition can not be separated from the domination of society with limited economic level and awareness of low clean and healthy life behaviour.